International Terrorism: Attributes of Terrorist Events, 1968-1977 (ITERATE 2) - Mickolus, Edward F. ([Verlag nicht ermittelbar], 1984)
This four-part study supersedes and substantially expands the coverage of terrorist incidents first reported in INTERNATIONAL TERRORISM: ATTRIBUTES OF TERRORIST EVENTS [ITERATE], which covered January 1970 through July 1973. This dataset contains four data files on 3,329 international terrorist attacks from 1968 through 1977. Part 1, Common File, includes information on the type of attack, the location of the beginning and end of the incident, the name of the terrorist group involved, and the numbers of deaths and injuries. Parts 2 and 3, Hostage and Fate Files, provide more detailed information on the characteristics and fates of both the hostages and the terrorists. Part 4, Skyjack File, consists of data on skyjacking incidents. Parts 2-4 can be linked to Part 1 when appropriate.